2015
DOI: 10.5603/piap.2015.0010
|View full text |Cite
|
Sign up to set email alerts
|

Zastosowanie Testu Aktywacji Bazofilów w Diagnostyce Nadwrażliwości na Kwas Acetylosalicylowy

Abstract: In the face of increasing prevalence of hypersensitivity reactions, introduction of effective, reliable and safe methods plays a crucial role in their diagnosing. Among the currently available laboratory (in vitro) methods is basophil activation test (BAT). It is a flow- cytometry based assay that allows to identificate in the blood sample basophils and additionally to asses the degree of cell activation after exposure to an antigen. The most common superficial identification markers are CD63 and CD203c, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Aktualnie coraz częściej rozważa się uzupełnienie standardowej diagnostyki o wykonanie BAT, szczególnie w przypadku alergii na leki i jad owadów [1]. Wartość diagnostyczna BAT w alergii na pokarmy jest alergenowo swoista i większość badań potwierdza dużą czułość i swoistość tej metody.…”
Section: Test Aktywacji Bazofilówunclassified
“…Aktualnie coraz częściej rozważa się uzupełnienie standardowej diagnostyki o wykonanie BAT, szczególnie w przypadku alergii na leki i jad owadów [1]. Wartość diagnostyczna BAT w alergii na pokarmy jest alergenowo swoista i większość badań potwierdza dużą czułość i swoistość tej metody.…”
Section: Test Aktywacji Bazofilówunclassified
“…BAT potentially may discriminate between IgE-mediated and IgE-non mediated allergy, although, as suggested by the Authors [1], non IgE-mediated allergy seems to be more frequently reported for drug hypersensitivity, for which sensitivity evaluation should be highly influenced. Interestingly, the Authors described a case report, a 52-years old patient, in whom hypersensitivity to NSAIDs was reported, in the absence of other allergologic signs, based on the CD63% FC expression in BAT (≥ 22%, c.o.…”
Section: To the Editormentioning
confidence: 99%
“…The recent article by Gawinowska et al, on the latest issue of "Polish Pneumology and Allergology" addressed the issue of the application of basophil activation test (BAT) in the diagnosis of drug hypersensitivity [1]. The Authors stressed on the commonly recognized role exerted by CD63 and CD203c markers in BAT, while existing further suggestions [2,3] but they never addressed the critical issue of basophil electronic capture in flow cytometry (FC), i.e.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations